PENGARUH KOMPOSISI MEDIA TERHADAP INISIASI TANAMAN APEL (Malus sylvestris Mill) - Sakka Samudin (Universitas Tadulako, 2009)
Apple development by vegetative propagation via tissue culture is an effort to reduce the import of apple. This experiment aimed to investigate media composition (cytokinin and NAA combination) suitable for initiation of apple. A Completely Randomized Design was employed, with four treatments i.e., : 3 ppm Benzylaminopurine (BAP) + 0.2 ppm NAA (P1), 4 ppm BAP + 0.2 ppm NAA (P2), 2 ppm kinetin + 0.2 ppm NAA (P3) and 3 ppm kinetin + 0.2 ppm NAA (P4), Parameters observed included number of shoots, leaves and nodes. Results of this experiment showed that the use of medium composition with 4 ppm BAP + 0.2 ppm NAA produced the most intensive shoot, leaf and node growth. However, medium composition with 3 ppm BAP + 0.2 ppm NAA had a good initiation quality.